MATERIAL, EDUCATIONAL, AND IDEOLOGICAL CHALLENGES OF TEACHING EFL WRITING AT THE TURN OF THE CENTURY - Leki, Ilona (International Journal of English Studies, 2001)
A great deal of literature on teaching English writing focuses primarily on English dominant contexts. The particular situation of writing instruction in non-English dominant countries has received insufficient attention, especially in light of some of the claims for the role of writing coming from the "center" countries. English language teachers, particularly those teaching in non-English dominant countries, who give substantial attention in their courses to teaching writing in English face a number of challenges. This article discusses two main categories of challenges. In the first group are challenges writing teachers face daily, such as class size, time constraints, accommodating local needs, and coping with problems connected to lack of both teacher experience in teaching L2 writing and student training in L1 writing. In the second group are challenges of a more ideological nature that are perhaps less obvious but more powerful and far-reaching, including the need to justify the large investment required on the part of institutions and individuals in order to teach L2 writing, the right to resist center imposed materials and methods, the need for dialogue with students about the role of writing in their lives, and the need to make L2 writing enhance learner options rather than limit them so that for learners, writing in L2 becomes not a pointless additional burden but a powerful means of accomplishing personal goals.